A novel electroactive λ-MnO2/PPy/PSS core–shell nanorod coated electrode for selective recovery of lithium ions at low concentration. Issue 36 (2nd September 2016) - Du, Xiao; Guan, Guoqing; Li, Xiumin; Jagadale, Ajay D.; Ma, Xuli; Wang, Zhongde; Hao, Xiaogang; Abudula, Abuliti
Abstract : A novel electroactive Li + ion-imprinted hybrid film consisting of λ-MnO2 /PPy/PSS core–shell nanorods is successfully fabricated on an electrode by using the unipolar pulse electrodeposition (UPED) technique. Abstract : A novel electroactive Li + ion-imprinted hybrid film consisting of λ-MnO2 /PPy/PSS core–shell nanorods is successfully fabricated on an electrode by using the unipolar pulse electrodeposition (UPED) technique. When the electrode is applied for selective electrochemical extraction of low concentrations of Li + ions from aqueous solutions via an electrochemically switched ion exchange (ESIX) process, the Li + ion adsorption capacity reaches 35.2 mg g −1 with an adsorption equilibrium time of less than 2 h. The excellent ion separation performance of this hybrid film should be attributed to its low ion transfer resistance due to its porous structure and the high electric driving force during the ESIX process. In particular, owing to the unique Li + ion imprinted vacant sites in the crystal structure of spinel λ-MnO2 nanorods, the selectivity factor for Li + /Na + reaches 46.0 with a molar ratio of 1 : 1. It is expected that this λ-MnO2 /PPy/PSS hybrid film can be applied as a promising electroactive material for effective separation of Li + ions from seawater.